Konowia Brauns, 1884, and Monoxiphia, n. gen. (Hymenoptera, Xiphydriidae): Palaearctic woodwasps with simple tarsal claws on all legs - Shinohara, Akihiko; Hara, Hideho (Zootaxa, 2021)
The Palaearctic xiphydriid genus Konowia Brauns, 1884, is redefined and the component species are revised on the basis of a close examination of stability and taxonomic use of previously used and newly introduced characters. A new genus, Monoxiphia, is proposed for Konowia harai Shinohara, 2019, from Japan (Monoxiphia harai (Shinohara, 2019), n. comb.) and Xiphydriola Semenov-Tian-Shanskij, 1921, is synonymized with Konowia. Konowia is represented by the following four species: K. betulae (Enslin, 1911) from Europe, through Siberia, Korea to Japan (Hokkaido, Kunashiri Is.), K. kojimai, n. sp., from Japan (Hokkaido, Honshu), K. megapolitana Brauns, 1884 from Europe to the Russian Far East, and K. yasumatsui (Togashi, 1972) from Japan (Honshu, Shikoku, Kyushu). Xiphydriola amurensis Semenov-Tian-Shanskij, 1921, and Platyxiphydria nishijimai Togashi, 1998, are synonymized with K. betulae and a new species, K. kojimai, is described from Japan. Konowia yasumatsui is newly recorded from Honshu and Shikoku and the male of this species is described for the first time. A key to separate Monoxiphia, Konowia and four Konowia species is provided.